Multiple Patients with Burn Injury Induced by a Chemical Explosion Managed by Physician-staffed Helicopters. Issue Volume 34:Issue s1(2019) (May 2019) - Yanagawa, Youichi; Kondo, Akihiko; Nagasawa, Hiroki; Takeuchi, Ikuto; Jitsuiki, Kei; Osaka, Hiromichi; Ishikawa, Kouhei; Omori, Kazuhiko
Abstract : Introduction: The management of chemical and explosive events is critical to reducing morbidity and mortality. However, initial patient care considerations and protective actions for staff are unfamiliar to most frontline clinicians. Methods: This study evaluated an Incident report. Results: On December 1, 2017, a factory of chemical industries in Japan exploded. Dust forming as a byproduct from the crushing and packing process of the resin for ink exploded at the facility. A local fire department requested the dispatch of two physician-staffed helicopters (known as a doctor helicopter [DH] in Japan). The first party of emergency services established a headquarters and first-aid station. However, this area was feared to be at risk of a second explosion. Physicians performed re-triage for all 11 burned patients. Three severely injured patients were transported to emergency medical service centers either by ground ambulance or the DH without undergoing any decontamination. The physician who escorted the patient by ground ambulance complained of a headache. One of the severely injured patients was treated at a local hospital and then transported to an emergency medical service center after undergoing decontamination and intubation. Fortunately, all patients who were transported to medical facilities obtained a survival outcome. Discussion: Chemical, biological, radiological, nuclear, and explosive incidents are rare, but can be fatal for responders to this kind disaster. As such, all who work at such scenes should be prepared and train adequately to ensure they have the knowledge and skill to both manage patients and protect themselves from harm.